2014
DOI: 10.30843/nzpp.2014.67.5740
|View full text |Cite
|
Sign up to set email alerts
|

Identification of weed seeds in soil samples intercepted at the New Zealand border

Abstract: Identification of weed seeds from overseas countries can be problematic particularly when diagnostic tools are lacking or incomplete A well trained seed analyst will usually be able to identify seed to generic level but not always to the species level Resources for identification of mature plants are usually more complete Using a seed germination method for intercepted soil samples achieved two goals; it provided an easier route to identification and a measure of viable seed The drawback of this method is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Assogbadjo et al [8] considered that seeds are the main cause of big differences can be shown by species, races, and families because all differences are in the seed which gives birth to the new plant. Each weeds species shows morphological characteristics different from the plant or other species, these morphological characteristics are not restricted to the external form of the plant only but it can be on level of different other parts of plant like fruit and seed [31].…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…Assogbadjo et al [8] considered that seeds are the main cause of big differences can be shown by species, races, and families because all differences are in the seed which gives birth to the new plant. Each weeds species shows morphological characteristics different from the plant or other species, these morphological characteristics are not restricted to the external form of the plant only but it can be on level of different other parts of plant like fruit and seed [31].…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…A key step when dealing with unknown invaders is correct taxonomic identification based on morphological and/or molecular characteristics, at least to genus and preferably to species level (James et al 2014;Kenis et al 2018). The more precise the identification, the more accurate the risk predictions can be.…”
Section: Sampling Methods Taxonomic Identification and Frequency Of mentioning
confidence: 99%
“…Brassica spp.) [ 6 , 21 ]. Only identifying contaminant seeds to the genus level can be problematic though when trying to assess the risk they pose [ 21 ].…”
Section: Introductionmentioning
confidence: 99%